2018
DOI: 10.1007/s00247-018-4192-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase acquisitions in pediatric abdominal-pelvic CT are a common practice and contribute to unnecessary radiation dose

Abstract: Multiphase acquisitions in routine contrast-enhanced CT of the abdomen and pelvis exams at outside imaging facilities are more frequent than those at a dedicated pediatric institution and contribute to unnecessary radiation dose. A contrast-enhanced CT of the abdomen and pelvis exam from an outside imaging facility with two passes may have as much as four times to six times the dose as the same exam performed with a single pass at a pediatric imaging center. We advocate for imaging facilities with high multiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The multiphase CT examinations are associated with much higher radiation doses as compared to the single-phase CT examinations in the same body region. Although single-center data on the use of multiphase routine chest and abdomen–pelvis CT from developed countries are available, 2,10 -16 there are little to no multi-institutional data from the developing countries. Thus, the purpose of our study was to assess the frequency, appropriateness, and radiation doses associated with multiphase CT protocols for routine chest and abdomen–pelvis examinations in 18 countries.…”
Section: Introductionmentioning
confidence: 99%
“…The multiphase CT examinations are associated with much higher radiation doses as compared to the single-phase CT examinations in the same body region. Although single-center data on the use of multiphase routine chest and abdomen–pelvis CT from developed countries are available, 2,10 -16 there are little to no multi-institutional data from the developing countries. Thus, the purpose of our study was to assess the frequency, appropriateness, and radiation doses associated with multiphase CT protocols for routine chest and abdomen–pelvis examinations in 18 countries.…”
Section: Introductionmentioning
confidence: 99%
“…And when CT examinations are performed in kids, we seem to continue to do the same old thing: multiphase scanning. This was highlighted in a recent article in Pediatric Radiology by Rostad et al [1]. Investigators compared abdominopelvic CT examinations performed at outside imaging facilities with those obtained at their practice (population of 939 abdominopelvic CTs) at a large children's hospital, for patients up to early 20s in age.…”
Section: The Landscapementioning
confidence: 99%
“…The authors showed that a change in practice from several interventions during that period resulted in a decrease from 35 additional phases in a sample of 50 abdominopelvic CTs in 2005 (1.7 average abdominal phases/scan) to 2 additional phases in 2010 (1.04 average phases/scan) [10]. Educational efforts can include notification of practices where multiphase scanning is relatively prevalent [1]. These efforts require resources, diplomacy and measured outcomes through follow-up initiatives.…”
Section: Bad Actorsmentioning
confidence: 99%
“…The ACR Dose Index Registry is a fabulous resource that provides for a much larger number of studies by pooling data from many institutions. Previous studies have focused on a single examination type performed at or referred (as outside studies) to a single institution (2)(3)(4)(5)(6)(7)(8). As noted by Strauss et al, the use of data from the ACR Dose Index Registry may have led to participation bias.…”
mentioning
confidence: 99%
“…Yet, we still have much to do. The study by Strauss et al ( 1) is but one more article showing that CT protocols and thus CT radiation doses differ in pediatric facilities versus those in adult facilities (2)(3)(4)(5)(6)(7)(8). How many more such articles will we see?…”
mentioning
confidence: 99%